America is in the heart a personal history - Bulosan, Carlos 1914-1956; Bulosan, Carlos 1914-1956. (Manila National Bookstore, 1946)
First published in 1946, this autobiography of the well known Filipino poet describes his boyhood in the Philippines, his voyage to America, and his years of hardship and despair as an itinerant laborer following the harvest trail in the rural West. Bulosan does not spare the reader any of the horrors tha accompanied the migrant's life; but his quiet, stoic voice is the most convincing witness to the terrible events he witnessed.t.
A reprint of the same edition published by Harcourt, Brace, New York.